EVALUASI KETEPATAN PENGOBATAN DISPEPSIA DI PUSKESMAS WILAYAH PESISIR KALIMANTAN TIMUR - Erfan Abdissalam; Aliah Ambarwati; Rizki Nur Azmi (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Farmasi Riau, 2026)
Dyspepsia is a prevalent digestive disorder marked by symptoms such as epigastric pain, nausea, vomiting, and a feeling of fullness after meals. Inadequate treatment can diminish the effectiveness of care and increase the likelihood of side effects. Consequently, assessing the appropriateness of dyspepsia treatment is essential to ensure the implementation of rational and effective therapy practices. This study aimed to assess the appropriateness of dyspepsia treatment based on five key parameters of treatment rationality: appropriate indication, medication, dosage, administration route, and timing of drug administration at the Muara Jawa Health Center in Kutai Kartanegara Regency. A descriptive observational approach utilizing a retrospective method was employed for this research. Data were extracted from the medical records of outpatients diagnosed with dyspepsia during the period from July to December 2024. A total of 200 samples were collected using purposive sampling techniques. The evaluation of treatments was conducted in accordance with the guidelines from the National Formulary, the Muara Jawa Health Center Formulary, and the National Consensus on Dyspepsia Management established by the Indonesian Gastroenterology Association (PGI). The results of the study indicated that the pharmaceutical treatments administered to dyspepsia patients at the Muara Jawa Health Center included PPI, H2RA, antacids, prokinetics, and sucralfate. Furthermore, the management of dyspepsia at this facility was deemed appropriate based on accuracy indicators, which encompassed correct indication, correct medication, correct dosage, correct administration route, and correct timing. To enhance the rational use of medications in accordance with national guidelines, regular monitoring and education for medical personnel are essential.